Mental health concerns related to COVID-19 outbreak in the middle-aged and elderly population: A web-based, cross-sectional survey from Haryana, North India - Jaison Joseph; Karobi Das; Suryakanti Dhal; Tamanna Sehrawat; Sweety Reshamia; Gazal Huria (Journal of Geriatric Mental Health, 2020)
Background: The coronavirus disease 2019 (COVID-19) pandemic is a global health emergency that could potentially have a serious impact on public health, including mental health. Elderly people are more vulnerable to the stress associated with the COVID-19 outbreak, and there is a dearth of epidemiological data on this issue. Aim: We conducted a web-based survey to evaluate the mental health concerns of middle-aged and elderly populations related to the COVID-19 outbreak from Haryana, India. Materials and Methods: An online survey was conducted from April 17 to May 01, 2020 using the principles of the snowball recruiting technique. The mental health concerns of the potential study participants were evaluated using the Hindi version of Patient Health Questionnaire-9 (PHQ-9) and General Anxiety Disorder-7 (GAD-7) scales. Results: There were a total of 1006 responses, out of which 266 were excluded from the analysis. The mean age of the participant was 58.68 (standard deviation [SD] = 8.05) years, and around 36' of respondents were the elderly with an age range of 60–79 years. The mean and SD of the GAD and PHQ were 2.51 (3.69) and 2.80 (4.86), respectively. The overall prevalence of anxiety and depressive symptoms was 19.7' and 21.5', respectively, (GAD-7 and PHQ-9 cutoff score of more than 05). We found a significant association between mental health outcomes with the presence of comorbid illness and physical activeness during the lockdown period. Conclusion: The present study represents a preliminary report on the psychological impact of the novel coronavirus outbreak in the Indian middle-aged and elderly community. The findings can be preliminary evidence for conducting a larger longitudinal study to guide policy-makers for subsequent research and clinical intervention strategy for mental health concerns related to COVID-19.